Pengaruh Positif Penggunaan Bingkai Diskon Terhadap Reputasi Merek, Citra Merek, Dan Minat Beli Ulang Di Toko Online Shopee - Lisda Anisa Putri; Albari Albari (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
The growth of e-commerce is increasing over time, it can be seen by the number of e-commerce that have sprung up. Shopee is one of the many e-commerce in Indonesia which has become the e-commerce with the most users in Indonesia. As the largest e-commerce company, marketing strategies play an important role in selling products, introducing products, and attracting consumers. This study aims to determine how influential discount framing as one of the marketing strategy used by Shopee has on brand reputation and brand image. In addition, it also determines whether consumer repurchase interest occurs due to these three factors. This research using a sample of 166 respondents spread across Indonesia. The sampling Technique uses convenience sampling. The analysis using the SEM method and processed using AMOS 24.0. The result of this study showed that there was a positive and significant influence between variables discount frame and brand image, discount frame and brand reputation, brand reputation and brand image, and brand image and repurchase intention. Meanwhile, the discount frame and brand reputation variables obtained results that were not significant in influencing the repurchase intention variable.